2005
DOI: 10.1111/j.1399-6576.2005.00841.x
|View full text |Cite
|
Sign up to set email alerts
|

Stroke volume of the heart and thoracic fluid content during head‐up and head‐down tilt in humans

Abstract: During both HUT and HDT, SV of the heart changed with the thoracic fluid content rather than with the central vascular pressures. These findings confirm that the function of the heart relates to its volume rather than to its so-called filling pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
62
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 41 publications
11
62
0
Order By: Relevance
“…Acute weightlessness did not decrease HR to below the 1-G control value, as expected compared with effects of simulation experiments, such as an upright-to-supine body posture change, head-down tilt, or head-out water immersion (4,9,13,14,17,26,28,29). One might speculate that a possible mechanism for the lack of a decrease in HR during 0 G could be that the preceding 1.8 G stimulated HR by activation of the sympathetic nervous system through inhibition of the baroreflexes, and that this activation counteracted the effects of the subsequent short-term 0-G phase.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Acute weightlessness did not decrease HR to below the 1-G control value, as expected compared with effects of simulation experiments, such as an upright-to-supine body posture change, head-down tilt, or head-out water immersion (4,9,13,14,17,26,28,29). One might speculate that a possible mechanism for the lack of a decrease in HR during 0 G could be that the preceding 1.8 G stimulated HR by activation of the sympathetic nervous system through inhibition of the baroreflexes, and that this activation counteracted the effects of the subsequent short-term 0-G phase.…”
Section: Discussionsupporting
confidence: 70%
“…The notion of a Bainbridge-like reflex is supported by our observations, when the subjects were supine, where the increase in CO during 0 G was purely a result of an unexpected increase in HR of 6 Ϯ 5 beats/min. This increase might theoretically have been initiated by a Bainbridge-like reflex, as previously suggested in studies concerning acute central volume loading by head-down tilt (5,28), or by intravenous infusion (3,22), and/or by mechanisms intrinsic to the heart, such as direct stretch of the sinus node (25), because our laboratory has previously shown that the transmural central venous pressure increases during 0 G in supine humans (29). This is also in accordance with previous water immersion observations by our laboratory (17), where HR was more suppressed during immersion to the midchest than to the neck, despite that central transmural filling pressures were higher during neck immersion.…”
Section: Discussionmentioning
confidence: 71%
“…HDT redistributes blood to the thoracic region, increasing central blood volume and cardiac filling pressures (8,31,32). In the present investigation, early mitral inflow and annular tissue velocities remained unchanged from the supine position with HDT, regardless of thermal condition.…”
Section: Diastolic Functionsupporting
confidence: 49%
“…If no compensatory cardiovascular changes occurred, the reduction in cardiac output due to pooling on standing would lead to a reduction of cerebral flow of this magnitude, and consciousness would be lost. In this study we used posture related physiological response to 10,13,14 that the stroke volume and cardiac output decreases on head up tilt by value almost by 40% of its supine value as measured by invasive and other methods. With our noninvasive easy to use method, we found this change as 36%, which is similar to it.…”
Section: Discussionmentioning
confidence: 99%
“…As measured by various other methods directly and indirectly, the cardiac output (CO) decreases 11 on an average by 25% and stroke volume (SV) decreases by 40% during the 70 0 head up tilt (HUT). However, from the supine position to 20 0 head down tilt (HDT), the CO and SV did not change significantly 10 . We have non-invasively measured the CO and SV during postural challenge with indigenous ICG equipment to test its ability to detect these changes on postural challenges.…”
Section: Introductionmentioning
confidence: 99%